Physical and mechanical properties of particleboard made from blends of kenaf (Hibiscus cannabinus L.) and rubberwood (Hevea brasiliensis Mull.Arg.) particle - Abd. Karim, Norani (2011)
Kenaf (Hibiscus cannabinus L.) variety V36 was used to make different types of particleboard. The purpose of this study was to evaluate the mechanical properties and dimensional stability of particleboards made from kenaf bast (KB), kenaf core (KC),rubberwood (RW) particles and a combination of the three. The basic properties of kenaf stem, namely, specific gravity (SG), moisture content (MC), pH and buffering capacity, wettability, and slenderness ratio (SL), were evaluated. Meanwhile, the mechanical properties, which include modulus of rupture (MOR), modulus of elasticity (MOE) and internal bonding strength (IB), dimensional stability (thickness swelling (TS) and water absorption (WA), as well as the density profile of the panels were determined according to JIS 5908:2003. Scanning electron micrographs (SEM) were setting characteristics, such as Urea Formaldehyde (UF). The results for the buffering capacity also showed that kenaf bast was the most resistant towards acid and alkali (19 minutes and 11 minutes, respectively) compared to kenaf core (14 minutes and 4 minutes) and rubberwood (10 minutes and 5 minutes). Meanwhile, when kenaf core and kenaf bast were mixed with rubberwood, the results obtained for the buffering capacity revealed that its curing rate was shortened when urea formaldehyde was used in the panel manufacturing and less hardener was also required. In more specific, higher wettability was found in the outer part of kenaf core compared to the other samples. The highest contact angle was found in the sample (1.040 for acid, 0.980 for alkali and 1.340 for distilled water). The finding also showed that kenaf bast had a longer slenderness ratio than kenaf core and rubberwood, with the values of 71.0, 3.5 and 6.8, respectively. In term of mechanical properties, the results showed that all the kenaf board types fulfilled the JIS for the minimum requirements for MOE (2000 MPa), except for 70%kenaf bast:30%rubberwood, 30%kenaf bast:70%rubberwood and 100%kenaf core. As for MOR, all the panels fulfilled the standard (8 MPa). Nevertheless, all the boards comprising kenaf bast did not fulfil the minimum requirement for IB. Scanning electron micrographs SEM showed that kenaf bast did not bond well with rubberwood. From the dimensional stability tests, the study showed that the most unstable panel was that made from 100% kenaf core, and this was followed by 70%:30% kenaf core:rubberwood and 30%:70% kenaf core:rubberwood. Except for 100%kenaf bast and 30%:70% kenaf bast:rubberwood, the remaining boards have a similar stabil swelling between 48-64% (respectively for 70%kenaf core:30%rubberwood and 100% kenaf core boards). The percentage of water absorption also improved between 76- 114%. The findings of the study proved that soaking the kenaf particles in LmwPF resin could improve the dimensional stability of kenaf boards, particularly for kenaf core. The usage of kenaf core up to 70% produced kenaf particleboards with a good quality.